Slidable atomic layers in van der Waals heterostructures. (23rd March 2017) - Kobayashi, Yu; Taniguchi, Takashi; Watanabe, Kenji; Maniwa, Yutaka; Miyata, Yasumitsu
Abstract: We report the preparation and manipulation of slidable atomic layers in clean, incommensurate van der Waals (vdW) heterostructures. Monolayer and multilayer WS2 grains are grown on graphite and hexagonal boron nitride (hBN) via chemical vapor deposition, and these grains can slide smoothly on graphite and hBN surfaces by manipulation with a tip. Furthermore, this sliding process allows the suspension, tearing, stacking, and connection of the atomic layers. These results demonstrate a novel approach for developing a wide variety of atomic-layer heterostructures with tunable interlayer coupling and an ideal system for studying the superlubricity of incommensurate, highly clean vdW contacts.